Metode Pelaksanaan Pekerjaan Bangunan Gedung Skywalk Pada Proyek Penataan Lapangan GGM Majalengka - Memen Sulaeman, Rangga Bayoe Pramoedjie (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2022)
In Indonesia, there are already many skywalks , one of which is at GGM Majalengka. Skywalk is used to make it easier for pedestrians to carry out activities. The function of GGM Majalengka is not only for the convenience of pedestrians, but also to provide convenience for shopping activities. The purpose of this study is to determine the implementation / steps for installing heavy steel structures and the stages of installation of precast concrete / precast concrete. The methods used to collect data are observation, interviews, observing working drawings, documentation and references from references. The results of this study found that the heavy steel work process consists of three stages of work, namely steel elevation plate work, steel column work, and steel beam work. The main materials used in the construction of the skywalk are heavy steel/WF sizes WF 350 and 300 and Precast Concrete/Precast Concrete 100x 400.